Differential Impact of Social and Monetary Reward on Procedural Learning and Consolidation in Aging and Its Structural Correlates - Doppler, Christopher E. J.; Meyer, Linda; Dovern, Anna; Stühmer-Beckh, Jaro; Weiss, Peter H.; Fink, Gereon R. (Frontiers in Aging Neuroscience, 2019)
In young (n = 36, mean ± SD: 24.8 ± 4.5 years) and older (n = 34, mean ± SD: 65.1 ± 6.5 years) healthy participants, we employed a modified version of the Serial Reaction Time task to measure procedural learning (PL) and consolidation while providing monetary and social reward. Using voxel-based morphometry (VBM), we additionally determined the structural correlates of reward-related motor performance (RMP) and PL. A monetary reward had a beneficial effect on PL in the older subjects only. In contrast, social reward significantly enhanced PL in the older and consolidation in the young participants. VBM analyses revealed that motor performance related to monetary reward was associated with larger grey matter volume (GMV) of the left striatum in the young, and motor performance related to social reward with larger GMV of the medial orbitofrontal cortex in the older group. The differential effects of social reward in young (improved consolidation) and both social and monetary rewards in older (enhanced PL) healthy subjects point to the potential of rewards for interventions targeting aging-associated motor decline or stroke-induced motor deficits.